The IRAIT project: Infrared astronomy from Antarctica - Tosti, Gino; Busso, Maurizio; Straniero, Oscar; Abia, Carlos; Bagaglia, Marco; Dolci, Mauro; Corcione, Leonardo; Nucciarelli, Giuliano; Roncella, Fabio; Valentini, Gaetano; Varano, Igor Di; PELUSI, DANILO (SPIE Proceedings, Ground-based Telescopes, 2004)
The Antarctica Plateau has recently turned out to be the best place on the Earth to perform astronomical infrared observations in the 2-20 um atmospheric windows and beyond, thanks to the extremely low sky background emission, the excellent atmospheric transparency and stability, the virtual absence of winds and the possibility of passively cooling the telescope and its focal plane instruments down to very low temperatures. Dome C, a site jointly exploited by Italian and French scientific teams in the framework of the Concordia project, lays on the Antarctica Plateau at an altitude of 3200m and presents exceptionally cold and dry climatic conditions. In this paper we shall describe the scientific motivations and the technical details of the infrared telescope IRAIT that we plan to put at Dome C starting from in 2005-2006. The IRAIT telescope is an alt-azimuth f/20 reflector, with a 0.8m parabolic primary mirror and a wobbling secondary mirror suitable for the specific techniques of IR observations. It will be equipped with a Near/Mid IR-camera built in Italy.